ASSEMBLED PRESSURE OF SHRINK FIT WITH MICRO DIMENSION AND CLOSED STRUCTURE - WANG GuoPing; CHENG Shuang; HAO HuaNing (Jixie qiangdu)
Contact pressure is stronger nonlinear along assembled length and hard to calculate in the interference fit with closed structure and micro dimension. A new method based on thin wall shell theory is presented to analyze the assembly pressure by solving integral equation. A simple model which is an assembly between thin wall cylinder with a fixed end and a rigid rotating shaft is solved. The results are compared with the results from ANSY,and in nice agreement. This method is easy to be applied on the design of the micro and high speed rotating machine.